مستوى تأثير الهياكلالرياضية المدرسية على تحقيق أهداف حصص التربية البدنية والرياضية من وجهة نظر أساتذة مرحلة التعليم الإبتدائي - أولاد سليمان إدريس; الشيخ المهدي (My University, 2024)
تهدف الدراسة إلى التعرف على مستوى تأثير الهياكل الرياضية المدرسية على تحقيق حصص التربية البدنية والرياضية من وجهة نظر أساتذة التعليم الإبتدائي ولهاذا الغرض تم إستخدام المنهج التحليل على عينة من 30 أستاذتعليم إبتدائي من ولاية غرداية تم إختيارها بشكل عشوائي ولحمع المعلومات إستخمنا آدات الإستبيان بعد حمع النتائج وتحلييلها
دارسة ميدانية على عينة من أساتذة التعليم الإبتدائي في ولاية غرداية
The study aims to identify the level of impact of school sports structures on the achievement of the goals of physical and sports education classes from the point of view of primary education professors. For this purpose, the curriculum was used on a sample of 30 primary education professors in the state of Ghardaia. The sample was selected at random and for data collection. results ", after collecting and statistically addressing the results: School sports structures significantly affect the achievement of physical and sports education classroom goals from the primary education professors' point of view, as these structures contribute to the achievement of both motor and cognitive and emotional sensory goals. Cognitively, sports structures contribute to the development of students' logical and evidentiary thinking, understanding of relationships and patterns, development of problem-solving skills, abstraction, generalization, communication and representation, as well as induction and deduction. Sports structures also play an important role in achieving emotional goals, helping to build self-confidence, develop patience and perseverance, enjoy puzzle solving, appreciate sports beauty, promote collaboration and teamwork, and sense of achievement. On this basis, the study recommended the integration of sports structures into physical and sports education classes, which has a significant positiveimpact on the achievement of the goals of these quotas in all respects, according to the view of primary education professors. This integration is essential to enhance the educational and educational process and achieve the desired results in an integrated manner.